INCLUSIVE EDUCATION AS A FORM OF HUMANIZED EDUCATION (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
Pedagogical problems between parents, students and personnel regarding the introduction of inclusive education are discussed in the article.